Non-invasive soccer goal line technology: A real case study - Spagnolo, P.; Leo, M.; Mazzeo, P. L.; Nitti, M.; Stella, E.; Distante, A. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2013)
In this paper, a real case study on a Goal Line Monitoring system is presented. The core of the paper is a refined ball detection algorithm that analyzes candidate ball regions to detect the ball. A decision making approach, by means of camera calibration, decides about the goal event occurrence. Differently from other similar approaches, the proposed one provides, as unquestionable proof, the image sequence that records the goal event under consideration. Moreover, it is non-invasive: it does not require any change in the typical football devices (ball, goal posts, and so on). Extensive experiments were performed on both real matches acquired during the Italian Serie A championship, and specific evaluation tests by means of an artificial impact wall and a shooting machine for shot simulation. The encouraging experimental results confirmed that the system could help humans in ambiguous goal line event detection.